Alloblennius frondiculus, a new species of blenny from the Andaman Islands(Teleostei: Blenniidae: Salariini) - Smith-Vaniz, William F.; Allen, Gerald R. (Zootaxa, 2012)
A new species of blenniid fish, tribe Salariini, is described based on a 23.8 mm SL specimen collected from the AndamanIslands, eastern Indian Ocean. It differs from other species of Alloblennius in having a pinnately branched supraorbitalcirrus about equal to eye diameter in height; lower jaws with relatively large, darkly pigmented labial flap anteriorly oneach side of chin; pectoral fin with 10 or 11 distinct, small dark spots; and anteriormost preopercular pore position with avertical pair of pores. The distribution of the new species is notable because the four previously described species of thegenus are known only from the western Indian Ocean and Red Sea. A table comparing the five species of Alloblennius is presented.